Aplikasi metode dhariah dalam UU No. 35/2014 tentang Perubahan atas UU Nomor 23 Tahun 2002 tentang Perlindungan Anak - Usep Saepullah (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
Cases of violence in Indonesia based on data from the National Commission for Child Protection (KPA), In 2012, reports of violence against children rose to 2,637, with the presentation of 62 percent of the sexual violence include the category of sexual harassment as many as 122 cases, regarded as one indicator of the poor quality of child protection , The existence of children who have not been able to live independently, of course, is in desperate need of people as a shelter. The government has sought legal protection for children, so that children can get a guarantee for the  continuity of life and living as part of human rights through the Act No. 23 of 2002 on Child Protection. The low quality of child protection in Indonesia, especially in sexual offenses and the amount of fines lot of criticism from various circles of society. The changes legislation relating relating to the protection of childrenfrom Law No. 23 of 2002 on the Protection of Children to Act No. 35 of 2014 about the amendment of Law No. 23 of 2002 on Child Protection contains a number of new perspectives (new paradigm) on the protection of children. One of the new paradigm it is the approach of preventing violence against children. In Islamic law approaches in child protection can be understood through the concept dhariah are sometimes prohibited form of preventive measures mentioned sadd al-dhariah, sometimes recommended even obliged called Fath al-dhariah. Methods dhariah in regulation Protection of Indonesian children develop in accordance with the development needs of the community through a new paradigm of Law No. 35 of 2014 on the Amendment of Act No. 23 of 2002 on Child Protection, on several things: the involvement of local governments in addition to the state, the government, society , families and the elderly, sexual crimes against children and restitution  compensation).